2023
DOI: 10.3390/livers4010001
|View full text |Cite
|
Sign up to set email alerts
|

The Pivotal Role of the Membrane-Bound O-Acyltransferase Domain Containing 7 in Non-Alcoholic Fatty Liver Disease

Preethi Chandrasekaran,
Ralf Weiskirchen

Abstract: Non-alcoholic fatty liver disease (NAFLD) is a common and prevalent disorder affecting 25 percent of the adults in the United States and 32 percent of adults globally. It is one of the common causes of chronic liver disease characterized by steatosis, which can lead to inflammation, fibrosis, and cirrhosis. NAFLD is strongly associated with obesity and insulin resistance. Multiple genetic variants have been consistently found to be associated with NAFLD; one of them is found in the TMC4-MBOAT7 loci. One varian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…Factors contributing to the pathogenesis of fatty liver disease include adipose tissue dysfunction/inflammation, the dysbiosis of the gut microbiota, and gut barrier function regulating several intrahepatic metabolic and inflammatory pathways. Therefore, probiotics and prebiotics may play a therapeutic role in fatty liver diseases by modulating the gut microbiome [ 115 ]. One study reported that the genetic sequencing of fecal samples from obese patients showed significantly fewer Bacteroidetes and more Firmicutes compared with lean volunteers [ 116 ].…”
Section: Probiotics and Obesitymentioning
confidence: 99%
“…Factors contributing to the pathogenesis of fatty liver disease include adipose tissue dysfunction/inflammation, the dysbiosis of the gut microbiota, and gut barrier function regulating several intrahepatic metabolic and inflammatory pathways. Therefore, probiotics and prebiotics may play a therapeutic role in fatty liver diseases by modulating the gut microbiome [ 115 ]. One study reported that the genetic sequencing of fecal samples from obese patients showed significantly fewer Bacteroidetes and more Firmicutes compared with lean volunteers [ 116 ].…”
Section: Probiotics and Obesitymentioning
confidence: 99%
“…70 Obesity, metabolic syndrome, and dyslipidemia are linked by insulin resistance in peripheral tissues, which leads to an increased hepatic flux of fatty acids from lipolysis and from adipose tissue that is resistant to the anti-lipolytic effects of insulin. 71,72 The hallmark feature of hypertriglyceridemia, due to increased FFA fluxes leads to hepatic accumulation of triglycerides. This, in turn, increases hepatic synthesis of VLDL hampering the lipolysis of chylomicrons and resulting in increased remnant triglycerides transported to the liver.…”
Section: Obesity and Dyslipidemiamentioning
confidence: 99%
“… 70 Obesity, metabolic syndrome, and dyslipidemia are linked by insulin resistance in peripheral tissues, which leads to an increased hepatic flux of fatty acids from lipolysis and from adipose tissue that is resistant to the anti‐lipolytic effects of insulin. 71 , 72 …”
Section: Signaling Pathways Involved In the Pathophysiology Of Obesit...mentioning
confidence: 99%
“…They store cholesterol esters and contain steroid hormones and triglycerides, which are used as an energy source and precursor for membrane phospholipid synthesis. 1,2 Under normal physiological conditions, hepatic lipid droplets are small and are limited in number. However, excessive hepatic lipid accumulation leads to an increase in the number and size of cytosolic lipid droplets.…”
Section: Introductionmentioning
confidence: 99%